An innovative approach to the study of hydrolysis of salts of the course of inorganic chemistry - Khamitova, Aina (Pedagogy and Psychology, 2022)
In this paper, the author considers the basic concepts and laws of hydrolytic processes, knowledge of which is necessary in many sections of chemistry. Innovative approaches are proposed in the study of the topic "Salt hydrolysis" using effective charges and electron shielding numbers. The values derived from Z eff for cations and neutral atoms of chemical elements of some groups, by which the hydrolysis of this salt can be estimated, are considered. The author notes that less shielding of the charges of the nuclei of the atoms of the elements increases their effective charges, as a result of which the attraction of the electronic layers to the nucleus increases, the so-called "d-compression" occurs. A similar compression is observed for f-elements, the effect of the polarizing action of cations and the polarizability of anions, as well as the strength of the hydrogen bond between water molecules and the hydrate shell is described. An effective method of using polarization potentials explaining the root cause of the polarizing ability of cations of some groups is recommended.